Α-Synuclein binds to cytoplasmic vesicles in U251 glioblastoma cells. (6th March 2017) - Duan, Jinyan; Ying, Zhengxin; Su, Yang; Lin, Fankai; Deng, Yulin
Highlights: α-Synuclein overexpression increases the oxidative stress in U251 cells. α-Synuclein overexpression alters cell surface and mitochondrial morphologies. α-Synuclein overexpression induces aggregation of cytoplasmic vesicles. H2 O2 increases the diameter of the cytoplasmic vesicles. Abstract: α-Synuclein is the major component of Lewy bodies, Lewy neurites, and glial cytoplasmic inclusions. It plays an important role in neurodegenerative diseases such as Parkinson's disease, multiple system atrophy, and other synucleinopathies. However, the pathogenesis and neurodegenerative effects of α-synuclein remain unknown. In this study, we established an α-synuclein and an α-synuclein-EGFP overexpressing U251 cell line. α-Synuclein overexpression increases oxidative stress and alters the cell surface and mitochondrial morphologies. We provide fluorescent-protein tagging, immunofluorescence and ultrastructural evidence showing that α-synuclein accumulations are associated with clusters of cytoplasmic vesicles and the diameter of these vesicles increases by H2 O2 in a time- and dose-dependent manner.